(untitled) (Al-Aasar, 2025)
Among the many challenges faced by Islam and Muslims in the contemporary era, one significant issue is the determination of Dar al-Harb and Dar al-Islam, the reconciliation between the two, and the legal rulings related to them. It is an established fact that this world has, since its inception, been divided into two realms. Referring to one as Dar al-Islam and the other as Dar al-Kufr would not be inaccurate. When Allah sent Adam (peace be upon him) to this world, He also sent Satan to the earth thereafter. From that moment began the ongoing struggle between good and evil, truth and falsehood, Islam and disbelief. As the world continued to evolve and progress, this division also witnessed developments, and new terminologies gradually came into existence. Among these, the concepts of Dar al-Islam and Dar al-Kufr or Dar al-Harb are especially worthy of attention. In this paper, we will explore the definition of the term Dar, the juristic categorization of the world into different ’Dars’ and examine the viewpoints of Islamic jurists (fuqaha) regarding this division. We will also evaluate whether this classification is universal and fixed (aafaqi) or based on juristic reasoning (ijtihadi), along with the evidence and arguments presented by the classical scholars. Furthermore, the paper will address a critical legal question: If a Muslim commits a Hadd-worthy offense (a crime liable to fixed punishment under Islamic law) while residing in Dar al-Harb, will the Hadd punishment be applied to him or not? What stance do the jurists of the Ummah hold on this matter